An idiotypic network model of AIDS immunopathogenesis. - Hoffmann, G W (1991)
Considerations from a network theory of the immune system suggest that human immunodeficiency virus and allogeneic stimuli may act synergistically to cause AIDS. The immune responses to these stimuli include two components that are directed against each other. In some AIDS risk groups other antigens that mimic major histocompatibility complex antigens may substitute for allogeneic stimuli. Implications for the prevention of AIDS are discussed.